Development of interactive multimedia learning based on articulate storyline for AutoCAD learning in basic vocational subjects at vocational high school - Busono , Tjahyani; Mardiana , Riskha; Pertiwi, Fitrina Aulia (Jurnal Pendidikan Teknologi Kejuruan, 2025)
This study aims to develop interactive multimedia learning based on Articulate Storyline for basic AutoCAD learning to overcome the limitations of the learning media used previously in basic vocational subject of Desain Pemodelan dan Informasi Bangunan (DPIB) program at SMK Negeri 1 Purwakarta. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model with systematic stages starting with analyzing problems, designing products, developing products , product testing and evaluation The research subjects involved two material experts, two media experts, and all class X DPIB students with a total of 98 people. The data collection instruments were expert validation questionnaires and student validation questionnaires with a likert scale. The validation results showed that the media obtained a feasibility percentage of 97% from material experts, 94% from media experts, and 81% from students, therefore the overall result was in the “very feasible” category. The main finding in this study is that an multimedia is deemed feasible for use in basic AutoCAD learning by taking into account the input from experts and students regarding program smoothness. The conclusion of this study confirms that the development of interactive multimedia learning based on Articulate Storyline with the ADDIE model is effective for use in AutoCAD practical learning in vocational high school and has the potential to improve the quality and motivation of student learning. This study is expected to motivate vocational school teachers to continue innovating in the development of learning media.